P2X7 Receptor in Bone Marrow-Derived Cells Aggravates Tuberculosis Caused by Hypervirulent Mycobacterium bovis - Bomfim, Caio César Barbosa; Amaral, Eduardo Pinheiro; Cassado, Alexandra dos Anjos; Salles, Érika Machado; do Nascimento, Rogério Silva; Lasunskaia, Elena; Hirata, Mario Hiroyuki; Álvarez, José Maria; D’Império-Lima, Maria Regina (Frontiers in Immunology, 2017)
Tuberculosis (TB) remains a serious public health problem despite the great scientific advances in recent decades. We have previously shown that aggressive forms of TB caused by hypervirulent strains of Mycobacterium tuberculosis and Mycobacterium bovis are attenuated in mice lacking the P2X7 receptor, an ion channel activated by extracellular ATP. Therefore, P2X7 receptor is a potential target for therapeutic intervention. In vitro, hypervirulent mycobacteria cause macrophage death by a P2X7-dependent mechanism that facilitates bacillus dissemination. However, as P2X7 receptor is expressed in both bone marrow-derived (BM) cells and lung structural cells, several cellular mechanisms can operate in vivo. To investigate whether the presence of P2X7 receptor in BM-derived cells contributes to TB severity, we generated chimeric mice by adoptive transfer of hematopoietic cells from C57BL/6 or P2X7-/- mice into CD45.1 irradiated mice. After infection with hypervirulent mycobacteria (MP287/03 strain of M. bovis), P2X7-/->CD45.1 mice recapitulated the TB resistance observed in P2X7-/- mice. These chimeric mice showed lower lung bacterial load and attenuated pneumonia compared to C57BL/6>CD45.1 mice. Lung necrosis and bacterial dissemination to the spleen and liver was also reduced in P2X7-/->CD45.1 mice compared to C57BL/6>CD45.1 mice. Furthermore, an immature-like myeloid cell population showing a Ly6Gint phenotype was observed in the lungs of infected C57BL/6 and C57BL/6>CD45.1 mice, whereas P2X7-/- and P2X7-/->CD45.1 mice showed a typical neutrophil (Ly6Ghi) population. This study clearly demonstrates that P2X7 receptor in BM-derived cells plays a critical role in the progression of severe TB.